Spermless males elicit large-scale female responses to mating in the malaria mosquito Anopheles gambiae. - Thailayil, J; Magnusson, K; Godfray, H; Crisanti, A; Catteruccia, F (2011)
Anopheles gambiae sensu stricto is the major vector of malaria, a disease with devastating consequences for human health. Given the constant spread of the disease, alternative approaches to the use of insecticides are urgently needed to control vector populations. Females of this species undergo large behavioral changes after mating, which include a life-long refractoriness to further insemination and the induction of egg laying in blood-fed individuals. Genetic control strategies aimed at impacting Anopheles fertility through the release of sterile males are being advocated to reduce the size of mosquito field populations. Such strategies depend on the ability of the released sterile males to mate successfully with wild females and to switch off the female receptivity to further copulation. Here we evaluate the role of sperm in regulating female behavioral responses after mating in An. gambiae. We developed spermless males by RNAi silencing of a germ cell differentiation gene. These males mated successfully and preserved standard accessory gland functions. Females mated to spermless males exhibited normal postcopulatory responses, which included laying large numbers of eggs upon blood feeding and becoming refractory to subsequent insemination. Moreover, spermless males induced transcriptional changes in female reproductive genes comparable to those elicited by fertile males. Our data demonstrate that, in contrast to Drosophila, targeting sperm in An. gambiae preserves normal male and female reproductive behavior for the traits and time frame analyzed and validate the use of approaches based on incapacitation or elimination of sperm for genetic control of vector populations to block malaria transmission.